3rd St. Gallen EORTC Gastrointestinal Cancer Conference: Consensus recommendations on controversial issues in the primary treatment of pancreatic cancer. (July 2017) - Lutz, Manfred P.; Zalcberg, John R.; Ducreux, Michel; Aust, Daniela; Bruno, Marco J.; Büchler, Markus W.; Delpero, Jean-Robert; Gloor, Beat; Glynne-Jones, Rob; Hartwig, Werner; Huguet, Florence; Laurent-Puig, Pierre; et al.
Abstract: The primary treatment of pancreatic cancer was the topic of the 3rd St. Gallen Conference 2016. A multidisciplinary panel reviewed the current evidence and discussed controversial issues in a moderated consensus session. Here we report on the key expert recommendations. It was generally accepted that radical surgical resection followed by adjuvant chemotherapy offers the only evidence-based treatment with a chance for cure. Initial staging should classify localised tumours as resectable or unresectable (i.e. locally advanced pancreatic cancer) although there remains a large grey-zone of potentially resectable disease between these two categories which has recently been named as borderline resectable, a concept which was generally accepted by the panel members. However, the definition of these borderline-resectable (BR) tumours varies between classifications due to their focus on either (i) technical hurdles (e.g. the feasibility of vascular resection) or (ii) oncological outcome (e.g. predicting the risk of a R1 resection and/or occult metastases). The resulting expert discussion focussed on imaging standards as well as the value of pretherapeutic laparoscopy. Indications for biliary drainage were seen especially before neoadjuvant therapy. Following standard resection, the panel unanimously voted for the use of adjuvant chemotherapy after R0 resection and considered it as a reasonable standard of care after R1 resection, even though the optimal pathologic evaluation and the definition of R0/R1 was the issue of an ongoing debate. The general concept of BR tumours was considered as a good basis to select patients for preoperative therapy, albeit its current impact on the therapeutic strategy was far less clear. Main focus of the conference was to discuss the limits of surgical resection and to identify ways to standardise procedures and to improve curative outcome, including adjuvant and perioperative treatment. Highlights: A summary of the expert discussions at the 3rd European Organisation for Research and Treatment of Cancer St. Gallen conference. Radical surgical resection followed by adjuvant chemotherapy offers the only evidence-based treatment with a chance for cure. Initial staging is used to classify localised tumours as resectable, borderline-resectable (BR) or unresectable tumours. The concept of BR tumours is considered as a good basis to select patients for preoperative therapy. Neoadjuvant therapy clearly has the potential to further improve long-term results, especially in BR tumours.